Increased Interleukin-17 and Glucocorticoid Receptor-β Expression in Interstitial Lung Diseases and Corticosteroid Insensitivity - Lo, Chun-Yu; Wang, Chun-Hua; Wang, Chih-Wei; Chen, Chih-Jung; Huang, Hung-Yu; Chung, Fu-Tsai; Huang, Yu-Chen; Lin, Chang-Wei; Lee, Chung-Shu; Lin, Chun-Yu; Lin, Chiung-Hung; Chang, Po-Jui; et al. (Frontiers in Immunology, 2022)
Background Treatment responsiveness to corticosteroids is excellent for cryptogenic organizing pneumonia (COP) and sarcoidosis, but suboptimal for idiopathic pulmonary fibrosis (IPF)/usual interstitial pneumonia (UIP). We hypothesise that the differential expression of IL-17 contributes to variable corticosteroid sensitivity in different interstitial lung diseases. Objective To determine the associations among expression of IL-17, glucocorticoid receptor-β and responsiveness to corticosteroid treatment in interstitial lung diseases. Methods Immunohistochemical (IHC) staining was performed on formalin-fixed paraffin-embedded (FFPE) lung tissues obtained by bronchoscopic, CT-guided or surgical biopsies, and quantified by both cell counting (% positive cells) by individuals and by software IHC Profiler plugin of ImageJ (opacity density score). We studied the effect of IL-17 on corticosteroid sensitivity in human fibroblast MRC5 cell line. Results Compared with specimens from patients with COP (n =13) and sarcoidosis (n =13), those from IPF patients (n = 21) had greater GR-β and IL-17 expression and neutrophil infiltration. Radiographic progression after oral corticosteroid treatment was positively correlated with the expression in IL-17 and GR-β/GR-α ratio in all patients (COP, sarcoidosis and IPF) and also within the IPF subgroup only. IL-17 expression level was positively associated with GR-β and GR-β/GR-α ratio. In MRC5 cells, exogenous IL-17 increased the production of collagen I and up-regulated GR-β expression and dexamethasone’s suppressive effect on collagen I production was impaired by IL-17, and silencing IL-17 receptor A gene attenuated the effect of IL-17. Conclusion Up-regulation of GR-β/GR-α ratio by IL-17 could be associated with the relative corticosteroid-insensitivity of IPF.